Promoting prevention with economic arguments - The case of Finnish occupational health services - Suhonen Aki; Kankaanpää Eila; Valtonen Hannu (BMC, 2008)
Abstract Background Both social and ethical arguments have been used to support preventive occupational health services (OHS). During the 1990s it became more common to support political argumentation for occupational health and safety by converting the consequences of ill health at work into monetary units. In addition, OHS has been promoted as a profitable investment for companies, and this aspect has been used by OHS providers in their marketing. Our intention was to study whether preventive occupational health services positively influence a company's economic performance. Methods We combined the financial statements provided by Statistics Finland and employers' reimbursement applications for occupational health services (OHS) costs to the Social Insurance Institution. The data covered the years 1997, 1999 and 2001 and over 6000 companies. We applied linear regression analysis to assess whether preventive OHS had had a positive influence on the companies' economic performance after two or four years. Results Resources invested in preventive OHS were not positively related to a company's economic performance. In fact, the total cost of preventive OHS per turnover was negatively correlated to economic performance. Conclusion Even if OHS has no effect on the economic performance of companies, it may have other effects more specific to OHS. Therefore, we recommend that the evaluation of prevention in OHS should move towards outcome measures, such as sickness absence, disability pension and productivity, when applicable, both in occupational health service research and in practice at workplaces.